Assessing Bone Type of Implant Recipient Sites by Stereomicroscopic Observation of Bone Core Specimens: A Comparison With the Assessment Using Dental Radiography. Issue 6 (1st June 2017) - Fu, Min‐Wen; Shen, E‐Chin; Fu, Earl; Lin, Fu‐Gong; Wang, Tian‐You; Chiu, Hsien‐Chung
Abstract : Background: The aim of the study is to determine if bone quality evaluation of surgically obtained bone core specimens using a stereomicroscope is reliable for determining bone quality at implant recipient sites. Methods: Bone quality was presurgically assessed in 122 edentulous ridges obtained from 62 patients using periapical radiographs and categorized according to the Lekholm and Zarb classification. During surgery, bone specimens were trephined, and bone types were immediately classified using a stereomicroscope. Microarchitectural characteristics of bone cores were evaluated after being scanned using microcomputed tomography (micro‐CT). Results: Bone types of implant sites categorized from radiography and stereomicroscope had statistically similar distribution but poor interrater agreement. Using micro‐CT, maxillae and mandibles showed significant differences in microarchitectural characteristics of bone cores. Bone volume (BV), total volume (TV), and trabecular thickness (Tb.Th) increased, whereas bone surface density (BS/BV) and open porosity (Po.[Op]) decreased in mandibular bone cores compared with those in maxillary bone cores. Moreover, micro‐CT values of BV/TV and Po.(Op) statistically correlated with bone types assessed by stereomicroscopy, particularly in mandibles (adjusted means of BV/TV of Type 2 to 4 versus Type 1 decreasing from −9.88%, −15.09%, −29.31%; those of Po.(Op) ranged from 9.77%, 15.06%, 29.52% in an upward trend). However, such correlations were not found in maxillae or when bone types were classified using periapical radiographs. Conclusions: Caution is needed when using presurgical periapical radiographs to predict bone quality at implant recipient sites. Surgically preserved bone core specimens, whenever obtainable, might offer additional information to accurately assess bone quality, particularly at mandibular implant sites.